Investigating Regulatory Compliance with Road Setback Requirements in Developmental Activities in the Anambra Capital Territory - Benedicta Njideka Okafor (Journal of Social Science and Economics (JOSSE), 2025)
This paper examined the essence of setbacks in sitting structures and buildings in Anambra Capital Territory (ACT). The aim is achieved through the objective, to determine the essence of setbacks in developmental projects in Anambra Capital Territory. As a result of non-compliance with road setbacks for development, ACT had become characterized by inadequate and deteriorated road network, walkways, unregulated building patterns, poor sanitation, uncontrolled street trading, mountains of garbage and chaotic transport system creating traffic and human congestion, noise pollution and overcrowding, among others. This work intends to address these issues and educate the citizens how road setbacks are essential. To achieve the stated aim, the study determined the essence of the sited structures to set standards in ACT. The foremost causes of non- compliance with road setbacks in ACT approved by professionals and non- professionals were also identified. The findings conclude that since there is a severe environmental effect in ACT, there is need for environmental education and awareness in the area, to educate the public on the importance of implementing road setbacks. When people understand the reasons for urban planning, they will be far less likely to violate the legal construction standards and will likewise make objections known.